2012
DOI: 10.1016/j.carres.2011.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Using In(III) as a promoter for glycosylation

Abstract: InCl3, InBr3, and In(OTf)3 were tested as promoters in the preparation of glycosides from trichloroacetimidate precursors. A range of protecting groups and of alcohol acceptors were used to determine the versatility of these promoters. Disaccharide formation was demonstrated. In most cases, the In(III) compounds were shown to promote glycosylation better than the widely used promoter BF3•OEt2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Et 2 O over TMSOTf for the activation of trichloroacetimidate or ( N ‐phenyl)trifluoroacetimidate donors, leading to the selective formation of 1,2‐ trans glycosides in high yields, has been widely studied . However, with more recent studies in 2012, Cloninger and co‐workers have established that In III salts serve as even better and more effective promoters than BF 3 ⋅Et 2 O for performing glycosylations with glycosylacetimidate donors . To establish the novelty of the salts, InCl 3 , InBr 3 , and In(OTf) 3 were reacted with various protecting‐group‐manipulated glycosyltrichloroacetimidate donors, and all of them led to the formation of the glycosylated products in high yields.…”
Section: Glycosylationsmentioning
confidence: 99%
“…Et 2 O over TMSOTf for the activation of trichloroacetimidate or ( N ‐phenyl)trifluoroacetimidate donors, leading to the selective formation of 1,2‐ trans glycosides in high yields, has been widely studied . However, with more recent studies in 2012, Cloninger and co‐workers have established that In III salts serve as even better and more effective promoters than BF 3 ⋅Et 2 O for performing glycosylations with glycosylacetimidate donors . To establish the novelty of the salts, InCl 3 , InBr 3 , and In(OTf) 3 were reacted with various protecting‐group‐manipulated glycosyltrichloroacetimidate donors, and all of them led to the formation of the glycosylated products in high yields.…”
Section: Glycosylationsmentioning
confidence: 99%
“…14 It should be noted that InBr 3 and other Lewis acids have been used in conjunction with the O-glycosylation of trichloroacetimidate donors. 15 We have previously reported the catalytic use of InBr 3 14 and other Lewis acids 16 to generate O-glycosides from weakly electrophilic peracetate sugars.…”
mentioning
confidence: 99%
“…Mattson et al reported the use of In­(III) salts as a catalyst for TCA activation in 2012. During their investigation, InCl 3 , InBr 3 , and In­(OTf) 3 were studied as novel catalysts in glycosylations.…”
Section: Glycosyl Imidate Donorsmentioning
confidence: 99%
“…94 In a later publication by the Iadonisi group in 2008, the synthesis of a pentasaccharide was completed in three steps starting from monosaccharide building blocks via Yb(OTf) 3 -and Bi(OTf) 3 catalysis of both TCA and N-phenyl trifluoroacetimidate (PTFA) donors. 106 Mattson et al 107 reported the use of In(III) salts as a catalyst for TCA activation in 2012. During their investigation, InCl 3 , InBr 3 , and In(OTf) 3 were studied as novel catalysts in glycosylations.…”
Section: Trichloroacetimidatesmentioning
confidence: 99%